Frontispiece: Fast Lithium Ion Conduction in Lithium Phosphidoaluminates. Issue 14 (20th March 2020) - Restle, Tassilo M. F.; Sedlmeier, Christian; Kirchhain, Holger; Klein, Wilhelm; Raudaschl‐Sieber, Gabriele; Deringer, Volker L.; van Wüllen, Leo; Gasteiger, Hubert A.; Fässler, Thomas F.
Abstract : Solid Electrolytes In their Research Article on page 5665, T. F. Fässler et al. describe the synthesis and properties of a novel low‐density material with fast lithium ion conduction. Graphic: Dr. Kerstin Mayer.